2022
DOI: 10.1177/17585732221131916
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation prior to total shoulder arthroplasty: A systematic review of outcomes and complications

Abstract: Background We conducted a review of current literature to examine the effects of smoking and smoking cessation on shoulder arthroplasty surgery. Methods A literature search was performed using the search terms “shoulder arthroplasty AND [smoke OR smoking OR tobacco OR nicotine].” Studies included English-language clinical outcomes studies on anatomic total shoulder arthroplasty (TSA), reverse TSA, and partial shoulder arthroplasty with evidence levels 1 through 4. Descriptive statistics calculated in the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…While there are studies suggesting that smoking should be stopped at least eight weeks before operations to minimize postoperative complications 11 , 12 , Warner et al 13 reported that smokers who quit smoking six months before an operation would be similar to non-smokers in terms of postoperative complications. Zhao et al 14 found that preoperative smoking cessation at least three weeks before surgery led to better postoperative pain outcomes, whereas Kamma et al 15 showed that patients who quit smoking at least one month preoperatively had better pain scores than current smokers. Based on these findings, in the present study, those who had not smoked for six months prior to the tympanomastoidectomy were included in the group consisting of non-smokers (Group 2).…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies suggesting that smoking should be stopped at least eight weeks before operations to minimize postoperative complications 11 , 12 , Warner et al 13 reported that smokers who quit smoking six months before an operation would be similar to non-smokers in terms of postoperative complications. Zhao et al 14 found that preoperative smoking cessation at least three weeks before surgery led to better postoperative pain outcomes, whereas Kamma et al 15 showed that patients who quit smoking at least one month preoperatively had better pain scores than current smokers. Based on these findings, in the present study, those who had not smoked for six months prior to the tympanomastoidectomy were included in the group consisting of non-smokers (Group 2).…”
Section: Discussionmentioning
confidence: 99%
“…These findings reiterate the importance of preoperative smoking cessation and counseling for patients to reduce the likelihood of readmission following TSA, which has been demonstrated in prior literature. 17 , 22 , 30 , 40 …”
Section: Discussionmentioning
confidence: 99%